Consolidation and Market Structure in Emerging Market Banking Systems - Gelos, R. (IMF Working Papers; Working Paper, 2002)
This paper examines the evolution of market structure in emerging market banking systems during the 1990s. While significant bank consolidation has been taking place in these countries, reflected in a sharp decline in the number of banks, this process has not systematically been associated with increased concentration as measured by standard indices. Moreover, econometric estimates based on the Panzar-Rosse (1987) methodology suggest that, overall, markets have not become less competitive in a sample of eight European and Latin American countries. Lowering barriers to entry, by doing such things as allowing increased participation of foreign banks, appears to have prevented a decline in competitive pressures associated with consolidation.